Effects of game location, quality of opposition and starting quarter score in the outcome of elite water polo quarters - Ruano, M. A.; Serna, A. D.; Lupo, C.; Sampaio, J. E. (The Journal of Strength and Conditioning Research, 2016)
The notational analysis is used to investigate teams' performance in water polo, especially focused on the determinants of success. Recently, a new topic has emerged "the situational variables," which includes the game conditions that may influence the performance at a behavioral level. The aim of this study was to identify the interactive effects of starting quarter score (SQS) (i.e., score difference at the beginning of each quarter and at the final score) and game location (GL) (i.e., home and away teams) in relation to quality of opposition (i.e., positions of difference between opposing teams at the end-of-season rankings) in elite men's water polo games. Data comprised 528 games (n = 2,112 quarters) from the first Spanish water polo division. A linear regression analysis was applied to show the impact of SQS and GL in relation to quality of opposition (unbalanced and balanced) for quarter (all quarters, and second, third, and fourth quarters). Results showed that SQS has an important effect for all quarters (0.16) and for the second (0.14) and third (0.14) quarters in balanced games (whereas the fourth quarter has an unpredictable outcome), and for each quarter (all quarters: 0.33; second quarter: 0.55; third quarter: 0.44; fourth quarter: 0.26) in unbalanced games. In addition, GL effects emerged for balanced (0.31) and unbalanced (0.45) games for all quarters and specifically for the second quarter of the unbalanced games. Therefore, this study showed that the elite water polo game dynamics, indirectly providing a reference for coaches (i.e., effective tactical approach) and physical trainers (i.e., high performance intensities), plans to improve their players' performance.